Integrated transcriptomic and metabolomic analyses reveal the involvement of AtGASA1 and AtGASA4 in salicylic acid pathway-associated immune responses in Arabidopsis - Jian-Bo Song; Ya-Ru Li; Zi-Xin Zhao; Xian-Zhi Zuo; Cai-Feng Wang; Min Huang; Shu-Fan Liu; Yu-Fan Chen; Wen-Qian Song; Lin Wang; Ying-Juan Wang; Xuan Huang (Plant Science, 2026)

Adaptive genetic trade-offs govern the enantioselective degradation and horizontal transfer of ibuprofen catabolic genes - Weihao Zhu; Mingli Jiang; Rui Fan; Kaihua Pan; Shenghao Wang; Lu Huang; Qiantong Ru; Yinhu Jiang; Qian Li; Qian Zhu; Mingliang Zhang; Zhijian Ke; et al. (Journal of Hazardous Materials, 2026)

Diniconazole leads to neurotoxicity in zebrafish via triggering TLR4/MyD88-mediated immune-inflammatory responses - Hongying Zhang; Ru Guo; Youjuan Wu; Jiajun Huang; Zijia Yin; Kaiwen Zhao; Xuefeng Liu; Meifeng Li; Zeyin Jiang; Shanghong Wang; Lihua Fan; Chengyu Hu; et al. (Fish & Shellfish Immunology, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

Heterolytic urea exchange-mediated thermal locking: Architecting 3D printed photo-mechanochromic smart elastomers - Min Yu; Yeting Huang; Dong Wang; Ru Song; Hanzhao Gong; Shuming Zhang; Xiaoyu Han; Yangzheng Li (Chemical Engineering Journal, 2026)

Facial width-to-height ratio predicts aggression and contest outcomes in wild golden snub-nosed monkeys - Pei Zhang; Yan-Ni La; Fei Niu; Jin-Bang Zhang; Paul A. Garber; Derek W. Dunn; Ru-Liang Pan; Kang Huang; Bao-Guo Li (Animal Behaviour, 2026)

Phytohormonal orchestration of plant phosphate starvation responses - Kai-Kai Lu; Ru-Feng Song; Yu-Pu Fan; Ling-Yu Xu; Bo-Hao Chen; Shu-Xian Li; Meng-Tian Sun; Guo-Mao Liu; Xiao-Li Huang; Lin Li; Xin-Ru Guo; Feng Ren; et al. (Journal of Plant Physiology, 2026)

Particulate matter-bound metals and chlorinated paraffins co-exposure: A population-based study on attention-deficit/hyperactivity disorder in Chinese youth - Ya-Qin Zhang; Qi Yang; Hai-Xin Tu; Haseeb Tufail Moryani; Wan-Ting He; Jing-Wen Huang; Dan-Yao Zhou; Yun-Ting Zhang; Li-Xia Liang; Yang Zhou; Li-Zi Lin; Wen-Wen Bao; et al. (Journal of Hazardous Materials, 2026)

Rubidium isotopes reveal no sub-arc melting of altered oceanic crusts in a cold subduction zone - Zi-Qiang Zhong; Ding-Sheng Jiang; Saskia Erdmann; Yi-Xiang Chen; Xia Hu; Zheng Xu; Wei Zhang; Jia-Ru Sheng; Wang-Ye Li; Fang Huang (Geochimica et Cosmochimica Acta, 2026)

LncRNA WFDC21P mediates the tobacco carcinogen induced malignant transformation of human normal lung epithelial cells by regulating tumor stemness - Shengsheng Li; Ru Liu; Shiyao Ye; Yitong Li; Linhan Huang; Qiuxian Wan; Zhuolin Liu; Yibo Wu; Nuoyan Wang; Minmin Huang; Jianjun Wu (Food and Chemical Toxicology, 2026)

From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.

Unraveling antibiotic fate in a highly urbanized estuary: Spatiotemporal patterns, multi-media partitioning, and contaminant prioritization - Nian-Nian Wu; Shan Liu; Ru Xu; Qian-Yi Huang; Yun-Feng Pan; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu; Xiao-Ping Huang (Marine Pollution Bulletin, 2026)

Effects of salinity and fermentation time on the microbial community, flavor, and metabolites of shrimp paste - Jing-ru Chen; Jia-bo Huang; Jing Li; Shi-meng Sun; Peng-fei Jiang (Food Research International, 2026)

Knowledge-infused hierarchical causal inference framework for decoding sludge settleability to quantitatively regulate multi-process wastewater treatment - Yucheng Li; Chen Cai; Feiyun Sun; Xiangfeng Huang; Kaiming Peng; Ru Guo; Jia Liu (Bioresource Technology, 2026)

A regional classification framework integrating AI and causal inference revealing the drivers of lake eutrophication in China - Yong Xu; Ru-Long Ma; Yu-Xi Feng; Bin Zou; Shen-Xin Li; Wen-Ting Huang; Shang-Chen Zhou; Wen-Qiang Peng (Water Research, 2026)

Wavelength-tunable light regulates binding affinity of histone deacetylase inhibitors via azobenzene Photoswitches - Yifan Ru; Sifan Guo; Yu He; Xiujuan Huang; Zhenguo Zhang; Lei Shi; Xiaoguang Shao; Zhong Li; Wen Fu; Xusheng Shao (Pesticide Biochemistry and Physiology, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

AtGASA1 positively regulates Arabidopsis response to salt stress by suppressing accumulation of reactive oxygen species - Jian-Bo Song; Hao-En He; Cai-Feng Wang; Xian-Zhi Zuo; Zi-Xin Zhao; Ya-Ru Li; Yu-Fan Chen; Shu-Fan Liu; Han-Wen Guo; Xuan Huang (Plant Cell Reports, 2026)

A facile identification strategy for coffee variety via the machine learning-assisted nanozyme sensor array - Jie Li; Xingna Zheng; Siyu Wang; Yi Ru; Yongxin Li; Hui Huang (Food Control, 2026)

LC-MS-based non-targeted metabolomics analysis of sea urchin during frozen storage under different packaging methods - Jia-bo Huang; Yi-hui Tang; Jing Li; Jing-ru Chen; Peng-fei Jiang (Food Chemistry, 2026)

Relationship of serum polycyclic aromatic hydrocarbon (PAHs) and lung function in adults: Evidence from a large community-based population in Guangzhou, China - Jing-Lin Zhang; Nuo Chen; Shui-Yue Lu; Michael S. Bloom; Shao Lin; Lu-Yin Wu; Li-Xia Liang; Yun-Ting Zhang; Jing-Wen Huang; Muhammad Amjad; Yong-Xiang Tang; Zhao-Huan Gui; et al. (Environmental Research, 2026)

Selective enrichment of nitrogen-metabolizing species in agricultural small water bodies: the potential regulation of additives from microplastics color - Qian Zhang; Xinhui Huang; Hongyu Shan; Peizhao Li; Jin Cui; Lishan Zhang; Shan Zhong; Xuan Ru; Zongchen Li; Xiaohua Shu (Bioresource Technology, 2026)

Short-, medium-, and long-chain chlorinated paraffins in sediments from the Pearl River Delta, China: Occurrence, sources, and risks - Fei-Xiang Xie; Yu-Fang Huang; Yong-Hong Zhang; Ya-Hui Xue; Run-Lin Chen; Xiao-Mei Huang; Hong-De Shi; Jia-Hui Huang; Hui-Ru Li (Science of The Total Environment, 2026)

Tree of life and conservation of gymnosperms in China - Chang-Wang Ma; Dan Xie; Hong Du; Kai-Yuan Huang; Yuan-Yuan Feng; Zhou-Rui Wei; Xin-Quan Liu; Cheng-Ru Li; Jing-Jing Sun; Xiao-Xin Wei; Zhi-Heng Wang; Wei-Hua Xu; et al. (Science China Life Sciences, 2026)

Optimizing the spatial configuration of scallop suspended cultivation net cages by leveraging seston flux variables based on the lattice Boltzmann hydrodynamics - Gangqin Tu; Haifei Liu; Zhiming Ru; Tao Sun; Wei Yang; Wei Huang; Li Cheng (Aquaculture, 2026)

Long-term ozone exposure and attention-deficit/hyperactivity disorder symptoms in school-aged children: Findings from a large multi-city study in China - Zhao-Huan Gui; Wan-Ting He; Yun-Ting Zhang; Joachim Heinrich; Michael S. Bloom; Shao Lin; Bin Jalaludin; Mohammed Zeeshan; Lidia Morawska; Tian-Yu Zhao; Shyamali Dharmage; Luke Knibbs; et al. (Journal of Hazardous Materials, 2026)

Associations of particulate matter size fractions and chemical composition with conjunctivitis and eczema: epidemiological evidence from the Pearl River Delta, China - Lu-Yin Wu; Mohammed Zeeshan; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Wen-Wen Bao; Yang Zhou; Muhammad Amjad; Li-Zi Lin; Ru-Qing Liu; Zhi Wang; Guang-Hui Dong (Environmental Research, 2026)

Quantitative resolution analysis in seismic imaging: From classical theory to cutting-edge advances - Jidong Yang; Jianping Huang; Hejun Zhu; Jiaxing Sun; Li-yun Fu; George McMechan; Houzhu Zhang; Ru-Shan Wu (Earth-Science Reviews, 2026)

Inhibition of the Microglial cGAS-STING Pathway Improves Neurological Deficits and Long-Term Hydrocephalus Symptoms in Mice with Intraventricular Hemorrhage - Hao-Xiang Wang; Hua-Jiang Deng; Kun-Hong Zhong; Zi-Ang Deng; Bao-Cheng Gao; Xin Tang; Yuan-You Li; Ke-Ru Huang; Ai-Ping Tong; Da-Xiong Feng; Liang-Xue Zhou (Molecular Neurobiology, 2026)

Natural and built environments and heart failure risk: An exposome-wide analysis in the UK Biobank - Xuewei Huang; Siyu Yin; Meng Yao; Fang Lei; Weifang Liu; Lijin Lin; Tao Sun; Yuanyuan Cao; Xingyuan Zhang; Ru Li; Liwen Wang; Yufeng Hu; et al. (Environmental Research, 2025)

Correction: Combining network Pharmacology and metabonomics to explore the mechanism of baicalin inhibiting PRRSV replication - Qin Luo; Yu-xuan Huang; Hai-rui Li; Chang-hong Qiao; Zhen-wen He; Xiang-yu Chen; Xiao-hu Wang; Gang Wang; Meng-meng Zhao; Ru-jian Cai (Veterinary Research Communications, 2025)

Combining network pharmacology and metabonomics to explore the mechanism of baicalin inhibiting PRRSV replication - Qin Luo; Yu-xuan Huang; Hai-rui Li; Chang-hong Qiao; Zhen-wen He; Xiang-yu Chen; Xiao-hu Wang; Gang Wang; Meng-meng Zhao; Ru-jian Cai (Veterinary Research Communications, 2025)

GZR101, a Novel Premixed Insulin for the Treatment of Diabetes Mellitus - Wei Chen; Cheng Cui; Wancai Xing; Yining Zhang; Anshun He; Yue Wang; Yan Huang; Nannan Zhai; Qimin Shi; Fangkai Xue; Yongchun Wang; Jun Zhang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Renal Denervation Improves Myocardial Mitochondrial Dysfunction and Myocardial Fibrosis by Inhibiting the NE/KLF15/renalase Pathway - Ye Chen; Ru Fu; Miao Huang; Tao Liu; Lixiong Zeng; Xiaogang Li (Molecular Neurobiology, 2025)

Transcriptome analysis reveals no obvious unintended effects in the spleen of CRISPR/Cas9-mediated CD163 and pAPN double-knockout pigs - Zhi-Guo Liu; Nan Wang; Wan-Jie Wang; Lei Huang; Shun-Shun Chi; Yu-Xin Nie; Mao-Sha Yuan; Ya-Ru Sun; Yu-Lian Mu; Kui Li (Functional & Integrative Genomics, 2025)

Association between legume consumption and risk of esophageal cancer among Chinese adults: a 17-year prospective cohort study - Fengyi Huang; Xiaorui Zhang; Jiayue Li; Xinqing Li; Ru Chen; Shaoming Wang; Fen Liu; Wenqiang Wei (Cancer Causes & Control, 2025)

Elucidating the impact of salt concentration on volatile flavor profiles and microbial dynamics in fermented cockle paste using GC-IMS and high-throughput 16S rDNA sequencing - Shi-meng Sun; Jia-bo Huang; Jing Li; Jing-ru Chen; Peng-fei Jiang (Food Research International, 2025)

Inhibition of the NLR pathway alleviates MAPK1 mutation-driven proliferation and differentiation deficits and enhanced apoptosis in P19 cells - Tingying Lei; Lei Liu; Fei Guo; Ru Li; Li Zhen; Fang Fu; Min Pan; Jin Han; Hang Zhou; Chunling Ma; Ruibin Huang; Xinyi Zhao; et al. (Tissue and Cell, 2025)

Salicylic acid promotes arsenic uptake in Pteris vittata via regulation of key genes and elevated nitric oxide and spermidine - Zhi-Hua Dai; Ze-Chao Li; Xi Chen; Ru Huang; Jian-Hua Sun; Chen-Jing Liu; Lena Q. Ma; Ru-Yi Yang (Journal of Hazardous Materials, 2025)

The threat of microplastics to human kidney health: Mechanisms of nephrotoxicity and future research directions - Ru-Yu Tan; Qin-Ying She; Yun-Ci Ma; Ming-Hong Liu; Li-Juan Li; Li-Li Huang; Yi-Wen Zhong; Hui-Xin Bi (Environmental Research, 2025)

Polycyclic aromatic hydrocarbon aggravates high-fat diet-induced metabolic dysfunction-associated steatotic liver disease through disturbing hepatocyte sphingolipid metabolism - Hui-Ru Kuo; Yu-Fen Chung; Li-Ting Wang; Chih-Wen Wang; Shih-Hsien Hsu; Li-Chen Chen; Ming-Hong Lin; Shau-Ku Huang; Kwei-Yan Liu (Environmental Pollution, 2025)

Interactions between soil and phyllosphere microbiomes modulate flavor formation of Qingxiang Tieguanyin Oolong Tea - Zhao Zhang; Xin-Rong Huang; Ming-Kang Jin; Le-Yang Yang; Jing-Jun Deng; Hu Li; Zhi-Ming Chen; Huo-Gui Su; Liang-De Xiao; Jin-Long Tang; Shun Li; Roy Neilson; et al. (Plant and Soil, 2025)

Genetic burden and multidimensional predictors in prenatal diagnosis of fetal congenital diaphragmatic hernia - Ruibin Huang; Fang Fu; Shanshan Mei; Liyuan Liu; Wei Zhong; Jin Han; Qiuxia Yu; Hang Zhou; Chunling Ma; Li Zhen; Min Pan; Qiong Deng; et al. (Human Genetics, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

An ultrasound-visualized methionine partitioning nano-modulator for enhanced immunotherapy against anti-PD-1 resistant tumors - Yingying Zhao; Beibei Zhang; Shaobo Duan; Yaqiong Li; Yuzhou Wang; Yongchao Wang; Juan Zhang; Rong Huang; Ru Jiang; Rui Zhang; Qi Zhou; Linlin Zhang; et al. (Chemical Engineering Journal, 2025)

Architectural features and antioxidative biofunctionality of a novel pectin from Angelica keiskei Koidz - Si-Ru Chen; Yu-Ru Zhu; Li-Ting He; Hong-Liang Sun; Jing Huang; Yan-Zi Yang; Hua-Jun Zhao; Bo Yang; Meng-Xia Yan (Natural Product Research, 2025)

Avian reovirus induces autophagy-mediated cargo of progeny viruses to extracellular vesicles and enhancement of virus release - Chao-Yu Hsu; Wei-Ru Huang; I.-Hsun Chiang; Jyun-Yi Li; Muhammad Munir; Hung-Jen Liu (Veterinary Microbiology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Incidence of respiratory diseases associated with per- and polyfluoroalkyl substances (PFAS) in PM2.5: New evidence from a population-based survey of Pearl River Delta (PRD), China - Lu-Yin Wu; Wan-Ting He; Mohammed Zeeshan; Yang Zhou; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Kun Zhao; Wen-Wen Bao; Li-Zi Lin; Zhao-Huan Gui; et al. (Journal of Hazardous Materials, 2025)

Thermophilic degradation of sulfamethazine by Geobacillus sp. S-07: pathway and mechanism - Ting Pan; Yan-Yan Zhou; Xu Huang; Jian-Xin Xu; Xiao-Yu Guo; Jian-Qiang Su; Hu Li; Xiao-Ru Yang (Environmental Research, 2025)

Schiff base crosslinking based dialdehyde-chitosan/gelatin/tea polyphenol electrospun nanofibrous membranes with excellent antibacterial and antioxidant activity for food packaging - Yu Ma; Ru Tian; Yudong Song; Mengxiao Liu; Jie Li; Zhichun Bi; Hui Huang; Yongxin Li (Food Packaging and Shelf Life, 2025)

Gelatin based preservation technologies on the quality of food: a comprehensive review - Qingfang Ying; Shengnan Zhan; Haixia Yu; Jihua Li; Ru Jia; Huamao Wei; Eugeni Roura; Xinle Tan; Zhaohui Qiao; Tao Huang (Critical Reviews in Food Science and Nutrition, 2025)

Efflux pumps of Pseudomonas aeruginosa and their regulatory mechanisms underlying multidrug resistance - Wen-Ru Li; Zhi-Qing Zhang; Kang Liao; Qing-Shan Shi; Xu-Bin Huang; Xiao-Bao Xie (International Biodeterioration & Biodegradation, 2025)

Combined exposure to atrazine and phoxim exacerbated the alterations of enzyme activity and abnormal gene expression in earthworms (Eisenia fetida) - Jinzhan Li; Jingwen Wang; Fang Shu; Nan Huang; Ru Jia; Yanhua Wang (Environmental Toxicology and Pharmacology, 2025)

Asymbiotic Nitrogen Fixation in the Phyllosphere of Urban Green Spaces - Jian-Feng Li; Le-Yang Yang; Zhao Zhang; Xin-Rong Huang; Hu Li; Shun Li; Xiao-Ru Yang (Current Microbiology, 2025)

Intensive rotational grazing has positive effects on productivity of rangeland - Ping Ge; Jianguo Xue; Yaqian Ru; Yulin Li; Dongxu Li; Peng Han; Ang Li; Jianhui Huang (Agriculture, Ecosystems & Environment, 2025)

Electrospun nanofiber membranes based on dialdehyde pullulan polysaccharide and schiff base crosslinked lysozyme for antibacterial packaging of blueberries - Yu Ma; Ru Tian; Yudong Song; Chenghui Yin; Hui Huang; Yongxin Li (Food Bioscience, 2025)

Chlorinated paraffins exposure in particulate matter increase the risk of attention-deficit/hyperactivity disorder symptoms in children and adolescents - Wan-Ting He; Jing-Wen Huang; Yun-Ting Zhang; Edwin Trevathan; Zhengmin Qian; Ri'enna Boyd; Michael Elliott; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; Guang-Hui Dong (Environmental Pollution, 2025)

Spatially confined Co nanoparticles in N doped carbon material for high efficiency capacitive deionization - Jianwei Wu; Yuzudi Tong; Xinhua Huang; Dongyin Qin; Ruikun Zhao; Ru Li; Guangzhi Hu (Desalination, 2025)

Leveraging Deep Learning to Extract Raindrop Size Gamma Distribution Parameters from Wind Profile Radar Data - Yu Huang; Zhiqun Hu; Lin Li; Ru Zhou; Xu Lu; Mengyu Huang (Journal of Meteorological Research, 2025)

Location optimization of unmanned aerial vehicle (UAV) drone port for coastal zone management: The case of Guangdong coastal zone in China - Jia Sun; Sijing Shu; Hongda Hu; Yingbin Deng; Zhao Li; Shengnan Zhou; Yue Liu; Minwen Dang; Wumeng Huang; Zhiwei Hou; Xiaoling Yin; Ru Zhang; et al. (Ocean & Coastal Management, 2025)

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

Study of the brittleness properties of granites under thermal and mechanical action through a new brittleness evaluation method - Huijun Lu; Ru Zhang; Li Ren; Anlin Zhang; Zidong Fan; Kun Xiao; Wei Liu; Tao Huang (Geothermics, 2025)

Mechanism of enhanced quality of Acetes chinensis powder-Alaska Pollock surimi: Gel properties, rheological properties, micro-structure - Qianqian Li; Jiehui Feng; Ru Jia; Huamao Wei; Tao Huang; Jinjie Zhang; Dalun Xu; Wenge Yang; Gaoshang Li (Food Research International, 2025)

Is there an association between eye-level greenness and childhood hypertension using street view? Findings from the Seven Northeastern Cities study in China - Huang-Min Yang; Jing-Yao Wang; Cheng Li; Ya-Qin Zhang; Ruoyu Wang; Qi Yang; Yao Yao; Zilong Wang; Shu-Li Xu; He-Hai Huang; Qian-Sheng Hu; Ru-Qing Liu; et al. (Environmental Research, 2025)

Polysaccharide modified fish gelatin intelligent hydrogels for reliable monitoring freshness of shrimp (Litopenaeus vannamei) - Qingfang Ying; Shengnan Zhan; Qiuyu Lu; Wenge Yang; Ru Jia; Gaoshang Li; Tao Huang (Food Hydrocolloids, 2025)

Chlorinated paraffins in particulate matter associated with asthma and its relative symptoms in school-aged children and adolescents: A cross-sectional survey in South China - Jing-Wen Huang; Wan-Ting He; Yun-Ting Zhang; Mo Yang; Nan-Xiang Jin; Ari Leskinen; Mika Komppula; Marjut Roponen; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Guang-Hui Dong; et al. (Science of The Total Environment, 2025)

Enhancing capacitive desalination efficiency via atomically dispersed Fe in N/P doped carbon material - Zhirou Wang; Xinhua Huang; Yuzudi Tong; Tong Wang; Mai Xu; Ru Li; Guangzhi Hu (Chemical Engineering Journal, 2025)

Automatic and integrated detection of nucleic acid by using a dual-mode thermal controlled digital microfluidic chip - Jiaqi Liao; Chonghao Li; Jiajia Liu; Hao Cheng; Linmin Li; Guixi Tang; Ru Huang; Yating Lu; Siyue Chen; Qian Zhang; Hao Chen; Qinyuan Chen; et al. (Analytica Chimica Acta, 2025)

Heavy metal emissions from on-road vehicles in Xia-Zhang-Quan metropolitan area in southeastern China from 2015 to 2060: impact of vehicle electrification - Zhe-Nan Wen; Qi-Yu Miao; Jiang-Ru Chen; Shui-Ping Wu; Li-Xiong He; Bing-Qi Jiang; Yi-Jing Liu; Zhi Huang (Environmental Science and Pollution Research, 2024)

Association of anthropogenic heat with asthma and related symptoms among children in China: A novel index reflecting climate change - Feng-Wen Shan; Xuan Liu; Ming-Kun Sun; Zhengmin Qian; Michael G. Vaughn; Niraj R. Chavan; Shu-Li Xu; He-Hai Huang; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; Li-Zi Lin; et al. (Sustainable Cities and Society, 2024)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Enhancing natural carbon sinks: Simulation of land use change under different carbon market scenarios by developing an ANN-ABM model - Ruimin Lin; Ru Guo; Yunyang Li; Guanghui Shao; Yuhao Zhang; Kaiming Peng; Xiangfeng Huang (Resources, Conservation and Recycling, 2024)

A novel hybrid variable cross layer-based machine learning model improves the accuracy and interpretation of energy intensity prediction of wastewater treatment plant - Yucheng Li; Chen Cai; Erwu Liu; Xiaofeng Lin; Ying Zhang; Hongjing Chen; Zhongqing Wei; Xiangfeng Huang; Ru Guo; Kaiming Peng; Jia Liu (Journal of Environmental Management, 2024)

A loss-of-function mutation in OsTZF5 confers sensitivity to low temperature and effects the growth and development in rice - Limin Wang; Ru Wang; Xin Cai; Huiqi Zheng; Yuxing Huang; Yuechen Li; Mingyue Cui; Mingli Lin; Huiwu Tang (Plant Molecular Biology, 2024)

PRDX1 Interfering Peptide Disrupts Amino Acids 70–90 of PRDX1 to Inhibit the TLR4/NF-κB Signaling Pathway and Attenuate Neuroinflammation and Ischemic Brain Injury - Xiang-Yu Ma; Cheng-yu Qi; Xing-yi Xu; Hui Li; Chang-Dong Liu; Xiang-Ru Wen; Yan-Yan Fu; Yan Liu; Jia Liang; Cheng-Yu Huang; Dan-Dan Li; Yan Li; et al. (Molecular Neurobiology, 2024)

Effect of Sodium Alginate and Calcium Chloride on the Physicochemical Characteristics of Shrimp (Penaeus Vannamei) Surimi Gels - Ziyan Wang; Jiehui Feng; Qianqian Li; Ru Jia; Tao Huang; Huamao Wei; Wenge Yang (Journal of Ocean University of China, 2024)

Impacts of food additives on gut microbiota and host health - Ping Li; Ru Qu; Ming Li; Ping Sheng; Liang Jin; Xiaochang Huang; Zhenjiang Zech Xu (Food Research International, 2024)

ESR chronology of the Quaternary sedimentary sequence of the Shinaimiao borehole in Hebi City, Henan Province, China - Hao Ji; Zhong-shan Shen; Chun-Ru Liu; Xiong-Nan Huang; Xiao-Ping Yang; Chuan-Yi Wei; Xin-Xiu Li; Qing Zhou; Gong-Ming Yin (Quaternary Geochronology, 2024)

Long-term ambient ozone exposure and childhood asthma, rhinitis, eczema, and conjunctivitis: A multi-city study in China - Zhao-Huan Gui; Zhan-Yu Guo; Yang Zhou; Shyamali Dharmage; Lidia Morawska; Joachim Heinrich; Zhang-Kai Cheng; Hui Gan; Zhi-Wei Lin; Dong-Ying Zhang; Jing-Wen Huang; Li-Zi Lin; et al. (Journal of Hazardous Materials, 2024)

Metabolic pathways altered by air pollutant exposure in association with coagulation function among the rural elderly - Haoyu Huang; Ru-Qing Liu; Yan Chen; Yuewei Liu; Guang-Hui Dong; Jian Hou; Shanshan Li; Yuming Guo; Chongjian Wang; Gongbo Chen (Journal of Hazardous Materials, 2024)

Combined effects of nitrogen limitation and overexpression of malic enzyme gene on lipid accumulation in Dunaliella parva - Shi-Yu Liang; Li-Hua Li; Meng-Xiang Ling; Lei Mo; Li-Mei Huang; Ling-Ru Ruan; Chang-Hua Shang (Bioresource Technology, 2024)

Bacterial functions are main driving factors on paddy soil organic carbon in both surface soil and subsoil - Xiang-Wen Huang; Jia-Jun Lin; De-Jin Li; Xiang-Qi Huang; Qi-Huan Xie; Sheng-Gang Pan; Xiang-Ru Tang; Jian-Ying Qi (Agriculture, Ecosystems & Environment, 2024)

Rapid, sensitive, and visual detection of pseudorabies virus with an RPA-CRISPR/EsCas13d-based dual-readout portable platform - Dong You; Tong Xu; Bing-Zhou Huang; Fang Wu; Li-Shuang Deng; Zhe-Yan Liu; Liang-Peng Ge; Zuo-Hua Liu; Jing Sun; Xiu Zeng; Yuan-Cheng Zhou; Si-Yuan Lai; et al. (Analytica Chimica Acta, 2024)

Asperidulins A and B, two new prenylxanthone derivatives from an apple-derived fungus Aspergillus nidulans KIB-HACM-01 - Peng Lai; Li Wang; Chenjie Deng; Yixin Xu; Xiao-Yan Ma; Chun-Ru Cheng; Sheng-Xiong Huang (Natural Product Research, 2024)

sp2-c linked Cu-based metal-covalent organic framework for chemical and photocatalysis synergistic reduction of uranium - Jin-Lan Liu; Mu-Xiang Lin; Juan Huang; Cheng-Rong Zhang; Jia-Xin Qi; Yuan-Jun Cai; Xiao-Juan Chen; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2024)

CIP1, a CIPK23-interacting transporter, is implicated in Cd tolerance and phytoremediation - Jiayi Wang; Huihui Zhu; Ru’nan Huang; Jiming Xu; Li Huang; Jianli Yang; Weiwei Chen (Journal of Hazardous Materials, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

Positive association between chlorinated paraffins and the risk of allergic diseases in children and adolescents - Jing-Wen Huang; Ya-Ying Bai; Dao-Sen Wang; Wan-Ting He; Jing-Lin Zhang; Hai-Xin Tu; Jing-Yao Wang; Yun-Ting Zhang; Qi-Zhen Wu; Shu-Li Xu; He-Hai Huang; Mo Yang; et al. (Journal of Hazardous Materials, 2024)

Redirecting surface reconstruction of CoP-Cu heterojunction to promote ammonia synthesis at industrial-level current density - Li Gan; Xiaoxue Zhang; Lei Guo; Muhammad Ajmal; Ru Jia; Xiaolei Guo; Chengxiang Shi; Lun Pan; Faryal Idrees; Xiangwen Zhang; Zhen-Feng Huang; Guidong Yang; et al. (Chemical Engineering Journal, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Next-generation sequencing of cerebrospinal fluid for the diagnosis and monitoring of neurocysticercosis - Jiexi Wen; Wen Su; Lei Zhang; Ru Huang; Jian Yin; Kai Li (Acta Neurologica Belgica, 2024)

Three new diterpenoids isolated from Euphorbia nematocypha Hand.-Mazz and their anti-fungal activity - Rong-Shuai Li; Zhi-Chang Xu; Ding-Mei Qin; Jia-Bi Huang; Meng-Ru Wang; Xue-Rong Zhao; Quan-Yu Yang; Wei-Lie Xiao; Rui-Rui Wang; Xiao-Li Li (Natural Product Research, 2024)

New insight into the bioaccumulation and trophic transfer of free and conjugated antibiotics in an estuarine food web based on multimedia fate and model simulation - Nian-Nian Wu; Shan Liu; Ru Xu; Qian-Yi Huang; Yun-Feng Pan; Heng-Xiang Li; Lang Lin; Rui Hou; Yuan-Yue Cheng; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

Density affects plant size in the Gobi Desert - Yonghua Li; Zhiming Xin; Bin Yao; Ruibing Duan; Xue Dong; Yanfeng Bao; Xinle Li; Yuan Ma; Yaru Huang; Fengmin Luo; Xing Li; Xu Wei; et al. (Science of The Total Environment, 2024)

Effect of marine heatwaves on juvenile greater amberjack (Seriola dumerili) - Yali Tian; Hang Li; Dongying Zhang; Chen Wang; Ruijuan Hao; Xiaoying Ru; Qin Hu; Yang Huang; Chunhua Zhu (Marine Environmental Research, 2024)

Steroid metabolites as overlooked emerging contaminants: Insights from multimedia partitioning and source–sink simulation in an estuarine environment - Ru Xu; Shan Liu; Yun-Feng Pan; Nian-Nian Wu; Qian-Yi Huang; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu; Yuan-Yue Cheng (Journal of Hazardous Materials, 2024)

Bacillus velezensis HY19 as a sustainable preservative in post-harvest citrus (Citrus reticulata Blanco L.) fruit management - Suping Li; Jingyu Hu; Shiqi Ning; Wei Li; Ru Jiang; Jianguo Huang; Yong Li (Food Control, 2024)

Global, regional, and national burden of ischemic heart disease attributable to ambient PM2.5 from 1990 to 2019: An analysis for the global burden of disease study 2019 - Li-Hao Guo; Li-Zi Lin; Yang Zhou; Bin Jalaludin; Lidia Morawska; Shyamali C. Dharmage; Luke D. Knibbs; Guo-Feng Huang; Duo-Hong Chen; Huimin Ma; Meng Gao; Joachim Heinrich; et al. (Environmental Research, 2024)

Urban green, blue spaces and their joint effect are associated with lower risk of emotional and behavior problem in children and adolescents, a large population-based study in Guangzhou, China - Jing-hong Liang; Ru-yu Yang; Mei-ling Liu; Ying-qi Pu; Wen-wen Bao; Yu Zhao; Li-xin Hu; Yu-shan Zhang; Shan Huang; Nan Jiang; Xue-ya Pu; Shao-yi Huang; et al. (Environmental Research, 2024)

Artificial light at night, MRI-based measures of brain iron deposition and incidence of multiple mental disorders - Jianbo Jin; Wenxing Han; Teng Yang; Zhihu Xu; Jin Zhang; Ru Cao; Yuxin Wang; Jiawei Wang; Xin Hu; Tiantian Gu; Fan He; Jing Huang; et al. (Science of The Total Environment, 2023)

Urban greenspace types influence the microbial community assembly and antibiotic resistome more in the phyllosphere than in the soil - Xin-Rong Huang; Roy Neilson; Le-Yang Yang; Jing-Jun Deng; Shu-Yi-Dan Zhou; Hu Li; Yong-Guan Zhu; Xiao-Ru Yang (Chemosphere, 2023)

Maternal transfer of F-53B inhibited neurobehavior in zebrafish offspring larvae and potential mechanisms: Dopaminergic dysfunction, eye development defects and disrupted calcium homeostasis - Luyin Wu; Mohammed Zeeshan; Yao Dang; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Yuan-Yuan Fan; Ming-Kun Sun; Tao Yu; Yue Wen; et al. (Science of The Total Environment, 2023)

Human TRMT1 catalyzes m2G or m22G formation on tRNAs in a substrate-dependent manner - Qing-Ping Xiong; Jing Li; Hao Li; Zhi-Xuan Huang; Han Dong; En-Duo Wang; Ru-Juan Liu (Science China Life Sciences, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

From arc accretion to within-plate extension: Geochronology and geochemistry of the Neoproterozoic magmatism on the northern margin of the Yangtze Block - Yu Huang; Xiao-Lei Wang; Jun-Yong Li; Ru-Cao Li; De-Hong Du; Chang-Hong Jiang; Lin-Sen Li; Ning Ding (Precambrian Research, 2023)

Environmental pollutant pre- and polyfluoroalkyl substances are associated with electrocardiogram parameters disorder in adults - Yuan-Yuan Fan; Chu Chu; Yun-Ting Zhang; Kun Zhao; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Lu-Yin Wu; Li-Zi Lin; Ru-Qing Liu; Wenru Feng; et al. (Journal of Hazardous Materials, 2023)

The association between childhood adiposity in northeast China and anthropogenic heat flux: A new insight into the comprehensive impact of human activities - Hong-Zhi Zhang; Dao-Sen Wang; Si-Han Wu; Guo-Feng Huang; Duo-Hong Chen; Hui-Min Ma; Yun-Ting Zhang; Li-Hao Guo; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; et al. (International Journal of Hygiene and Environmental Health, 2023)

First transcriptome profiling in gill and hepatopancrease tissues of Metapenaeus ensis in response to acute ammonia-N stress - Yun-Dong Li; Meng-Ru Si; Shi-Gui Jiang; Qi-Bin Yang; Song Jiang; Li-Shi Yang; Jian-Hua Huang; Fa-Lin Zhou (Fish & Shellfish Immunology, 2023)

A marine lipopeptides-producing Bacillus amyloliquefaciens HY2-1 with a broad-spectrum antifungal and antibacterial activity and its fermentation kinetics study - Lin-ru Huang; Xiao-ning Ling; Shuai-ying Peng; Ming-hui Tan; Lu-qi Yan; Ying-yin Liang; Gang-hui Li; Kun-tai Li (World Journal of Microbiology and Biotechnology, 2023)

Soil extracellular enzymes characteristics and their controlling factors along the elevation gradient in Qinghai-Tibet Plateau, China - Yan-xia Pan; Xin-rong Li; Zeng-ru Wang; Li Feng; Lei Huang; Bing-yao Wang; Jing-yao Sun (Applied Soil Ecology, 2023)

Xanthine-derived reactive oxygen species exacerbates adipose tissue disorders in male db/db mice induced by real-ambient PM2.5 exposure - Leijian Chen; Huankai Li; Yi Ru; Yuanyuan Song; Yuting Shen; Lifang Zhao; Gefei Huang; Yi Chen; Zenghua Qi; Ruijin Li; Chuan Dong; Jiacheng Fang; et al. (Science of The Total Environment, 2023)

Enhancement of Zn-N-C charge-directed rearrangement for high-performance selectivity of heavy metal ions in capacitive deionization - Xinhua Huang; Zhirou Wang; Xiaonan Li; Dongyin Qin; Meiyue Jin; Yuzudi Tong; Ru Li (Desalination, 2023)

Highly sensitive plasmonic biosensor for hepatitis B virus DNA based on the surface etching of the active helical gold nanorods - Ru Cheng; Liang Tong Li; Min Huang; Fu Zhu; Qian Li; Hui Liu; Jie Gao; Xiao Hui Zhao; Fu Kang Luo; Jian Wang (Chemical Engineering Journal, 2023)

Associations of long-term joint exposure to various ambient air pollutants with all-cause and cause-specific mortality: evidence from a large population-based cohort study - Zhi-Hao Li; Xiao-Meng Wang; Jia-Xuan Xiang; Ying Nan; Ying-Jun Chen; Pei-Dong Zhang; Dan Liu; Dong Shen; Xi-Ru Zhang; Wen-Fang Zhong; Pei-Liang Chen; Qing-Mei Huang; et al. (Environmental Science and Pollution Research, 2023)

Comparative Physiological and Transcriptomic Analysis Provide New Insights of Crucial Pathways and Genes Regulating Kenaf Salt Tolerance - Yali Hu; Zengqiang Li; Meiqiong Tang; Dengjie Luo; Muhammad Haneef Kashif; Shan Cao; Caijin Wang; Jiao Yue; Zhen Huang; Jiao Pan; Xia Wu; Qijing Wu; et al. (Journal of Plant Growth Regulation, 2023)

Prenatal diagnosis in the fetal hyperechogenic kidneys: assessment using chromosomal microarray analysis and exome sequencing - Ruibin Huang; Fang Fu; Hang Zhou; Lu Zhang; Tingying Lei; Ken Cheng; Shujuan Yan; Fei Guo; You Wang; Chunling Ma; Ru Li; Qiuxia Yu; et al. (Human Genetics, 2023)

Free and conjugated forms of metabolites are indispensable components of steroids: The first evidence from an estuarine food web - Shan Liu; Ru Xu; Yun-Feng Pan; Qian-Yi Huang; Nian-Nian Wu; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu (Water Research, 2023)

An extended SW-TES algorithm for land surface temperature and emissivity retrieval from ECOSTRESS thermal infrared data over urban areas - Chen Ru; Si-Bo Duan; Xiao-Guang Jiang; Zhao-Liang Li; Cheng Huang; Meng Liu (Remote Sensing of Environment, 2023)

Electrochemical etching induced high-valence cobalt with defects site for boosting electrochemical water splitting - Hongmei Gao; Jiaqi Liu; Zijin Zhang; Yuxuan Lu; Ru Chen; Yu-Cheng Huang; Chao Xie; Mengyi Qiu; Tianyu Wu; Jinbo Wang; Yubin Jiang; Chung-Li Dong; et al. (Chemical Engineering Journal, 2023)

Characterization of microbial community, ecological functions and antibiotic resistance in estuarine plastisphere - Le-Yang Yang; Xin-Rong Huang; Roy Neilson; Shu-Yi-Dan Zhou; Zhao-Lei Li; Xiao-Ru Yang; Xiao-Xuan Su (Science of The Total Environment, 2023)

Plant identity shapes phyllosphere microbiome structure and abundance of genes involved in nutrient cycling - Jian Li; Ming-Kang Jin; Roy Neilson; Shi-Lin Hu; Yi-Jia Tang; Zhao Zhang; Fu-Yi Huang; Jing Zhang; Xiao-Ru Yang (Science of The Total Environment, 2023)

Whole exome sequencing improves genetic diagnosis of fetal clubfoot - Ruibin Huang; Hang Zhou; Chunling Ma; Fang Fu; Ken Cheng; You Wang; Ru Li; Tingying Lei; Qiuxia Yu; Dan Wang; Shujuan Yan; Xin Yang; et al. (Human Genetics, 2023)

How Comamonas testosteroni and Rhodococcus ruber enhance nitrification in the presence of quinoline - Ge Zhu; Haiyun Zhang; Ru Yuan; Meng Huang; Fei Liu; Mo Li; Yongming Zhang; Bruce E. Rittmann (Water Research, 2023)

Synthesis of cationic polymer decorated with halogen for highly efficient trapping 99TcO4-/ReO4- - You-Gan Wang; Qing-Hua Hu; Juan Huang; Wei Jiang; Li Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Effect of phenol formaldehyde-associated microplastics on soil microbial community, assembly, and functioning - Hu Li; Qiu-Ping Luo; Sha Zhao; Yan-Yan Zhou; Fu-Yi Huang; Xiao-Ru Yang; Jian-Qiang Su (Journal of Hazardous Materials, 2023)

Ultrastructure and distribution of antennal sensilla of Bombus terrestris (Hymenoptera: Apidae) - Xi Huang; Xi-lian Xu; Ru-xu Li; Su Wang; Li-xia Tian (Zoologischer Anzeiger, 2023)

Zero-valent iron boosts nitrate-to-ammonia bioconversion via extracellular electron donation and reduction pathway complementation - Xue Li; Jie Li; Xiao-Rong Yu; Yong-Kun Zhu; Hou-Qi Liu; Lin Chen; Jing Wu; Xian-Zhong Fu; Shuo Cui; Tian-Yin Huang; Ru-Quan Ye; Wen-Wei Li (Resources, Conservation and Recycling, 2023)

Luteolin ameliorates palmitate-induced lipotoxicity in hepatocytes by mediating endoplasmic reticulum stress and autophagy - Chun-Yin Huang; Haw-Wen Chen; Chia-Wen Lo; Yu-Ru Wang; Chien-Chun Li; Kai-Li Liu; Chong-Kuei Lii (Food and Chemical Toxicology, 2023)

Air pollution, greenness and risk of overweight among middle-aged and older adults: A cohort study in China - Wenxing Han; Zhihu Xu; Xin Hu; Ru Cao; Yuxin Wang; Jianbo Jin; Jiawei Wang; Teng Yang; Qiang Zeng; Jing Huang; Guoxing Li (Environmental Research, 2023)

Recyclable nanocomposites for carbon dioxide fixation and membrane separation using waste polycarbonate - Ying-Chi Huang; Li-Fan Chen; Yu-Hsiang Huang; Chien-Chieh Hu; Chien-Hsin Wu; Ru-Jong Jeng (Chemical Engineering Journal, 2023)

Citric acid-based deep eutectic solvent (CA-DES) as a new soil detergent for the removal of cadmium from coking sites - Jie Qian; Ying-hua Li; Fei Su; Ji-guo Wu; Jia-ru Sun; Tian-ci Huang (Environmental Science and Pollution Research, 2023)

Cryo-EM structures reveal the dynamic transformation of human alpha-2-macroglobulin working as a protease inhibitor - Xiaoxing Huang; Youwang Wang; Cong Yu; Hui Zhang; Qiang Ru; Xinxin Li; Kai Song; Min Zhou; Ping Zhu (Science China Life Sciences, 2022)

The central role of GmGLP20.4 in root architecture modifications of soybean under low-nitrogen stress - Wei Wang; Jiajia Li; Muhammad Nadeem; Jianxin Wang; Ru Huang; Qian Liu; Wenqiao Fan; Haowei Zheng; Long Yan; Xiaobo Wang (Theoretical and Applied Genetics, 2022)

PITPNC1 promotes the thermogenesis of brown adipose tissue under acute cold exposure - Guoqing Tang; Chengxin Ma; Liangkui Li; Shaoyan Zhang; Fengsheng Li; Jin Wu; Yesheng Yin; Qing Zhu; Yan Liang; Ru Wang; He Huang; Tong-Jin Zhao; et al. (Science China Life Sciences, 2022)
Brown adipose tissue (BAT) plays an essential role in non-shivering thermogenesis. The phosphatidylinositol transfer protein, cytoplasmic 1 (PITPNC1) is identified as a lipid transporter that reciprocally transfers phospholipids between intracellular membrane structures. However, the physiological significance of PITPNC1 and its regulatory mechanism remain unclear. Here, we demonstrate that PITPNC1 is a key player in thermogenesis of BAT. While Pitpnc1 −/− mice do not differ with wildtype mice in body weight and insulin sensitivity on either chow or high-fat diet, they develop hypothermia when subjected to acute cold exposure at 4°C. The Pitpnc1 −/− brown adipocytes exhibit defective β-oxidation and abnormal thermogenesis-related metabolism pathways in mitochondria. The deficiency of lipid mobilization in Pitpnc1 −/− brown adipocytes might be the result of excessive accumulation of phosphatidylcholine and a reduction of phosphatidic acid. Our findings have uncovered significant roles of PITPNC1 in mitochondrial phospholipid homeostasis and BAT thermogenesis.

Discovery of the oncogenic MDM2, a direct binding target of berberine and a potential therapeutic, in multiple myeloma - Chuting Li; Ru Su; Xiuyuan Wang; Guiping Huang; Yanjun Liu; Juhua Yang; Zhao Yin; Chunming Gu; Jia Fei (Functional & Integrative Genomics, 2022)

Vibrio salinus sp. nov., a marine nitrogen-fixing bacterium isolated from the lagoon sediment of an islet inside an atoll in the western Pacific Ocean - Wei-Sheng Huang; Li-Ting Wang; Jwo-Sheng Chen; Yen-Ting Chen; Sean Ting-Shyang Wei; Yin-Ru Chiang; Pei-Ling Wang; Tzong-Huei Lee; Shih-Ting Lin; Lina Huang; Wung Yang Shieh (Antonie van Leeuwenhoek, 2022)

Why empresses have more sons? Maternal instant social condition determines it - Yan-Peng Li; Wei Ding; Zhi-Pang Huang; Ru-Liang Pan; Na Li; Guo-Peng Ren; Liang-Wei Cui; Qing-hua Cai; Wen Xiao (Behavioral Ecology and Sociobiology, 2022)
Sexual selection echoed by the sex ratio is a critical issue in evolution and reproductive biology studies, and the second sex ratio (sex ratio at birth, SRB) is an important evaluation indicator for sex regulation. However, broad debates on sex ratio at birth exist due to the lack of a clear spatiotemporal genealogical database. This study explicitly tests the Trivers and Willard’s hypothesis stating that parents with good social conditions tend to show a male-biased SRB. Using a database of Chinese imperial families from 211BC to 1912 (2142 years) which avoids the spatiotemporal confusion of data thanks to its clear boundaries and long timespan, we found that a proportion of males at birth was 0.54. In particular, the results indicate that the empresses generated a significantly higher male-biased SRB than the concubines within the imperial harems (0.61 vs 0.53), while the SRB of concubines was not higher than ordinary people (0.53 vs 0.52). A significant difference of SRB before and after empress coronation (0.48 vs 0.65) was detected, indicating that the change to a higher social status is the leading cause of a biased SRB. These findings suggest that mothers with privileged instant social conditions tend to generate more boys than girls. In other words, a higher maternal social rank during the conception period, instead of rich resources, forms the primary mechanism regulating the SRB. Significance statement Adaptive sex ratio has been a debatable topic difficult to clearly verify since the publication of Trivers and Willard Hypothesis in 1973, which proposes that parents who have good conditions should produce more male offspring. The one reason is that the validity and sample size of the databases used contained unavoidable confounding noise, both genealogically and genetically. To overcome these issues, we specifically compiled a historical database of Chinese imperial families, which are characterized by a confined mating harem and unique eunuch system, guaranteeing biological and genetic purity with precise genealogical relationships and genetic linkages between the parents and the offspring. Thus, this is an extraordinary effort to clarify the hypotheses proposed by TWH and other hypotheses.

Lelliottia steviae sp. nov. isolated from Stevia rebaudiana Bertoni - Jing Lin; Ke Huang; Jing-Yu Huang; Yuan-Ru Xiong; Meng-Meng Wei; Na Xiao; Jia Gao; Xuan-Kai Ding; Zi-Yang Ma; Jun-Hao Sang; Ling-Xian Kong; Zhi-Yun Hong; et al. (Archives of Microbiology, 2022)

Dataset-based assessment of heavy metal contamination in freshwater fishes and their health risks - Xiao-Bo Liu; Congtian Lin; Yang-Yu Wu; Hai-Ning Huang; Li-Ting Zhu; Ru Jiang; Qiansheng Huang (Environmental Science and Pollution Research, 2022)

Inhibition of neurogenic contractions in renal arteries and of cholinergic contractions in coronary arteries by the presumed inhibitor of ADP-ribosylation factor 6, NAV2729 - Ru Huang; Bingsheng Li; Alexander Tamalunas; Raphaela Waidelich; Christian G. Stief; Martin Hennenberg (Naunyn-Schmiedeberg's Archives of Pharmacology, 2022)
NAV2729 is a presumed inhibitor of the monomeric GTPase ADP ribosylation factor 6 (ARF6) and inhibits smooth muscle contraction outside the cardiovascular system. Its effects on vascular smooth muscle contraction or a possible role of ARF6 in vasocontraction have not yet been examined. Here, we report effects of NAV2729 on neurogenic and agonist-induced contractions in renal interlobar and coronary arteries. Contractions of pig interlobar and coronary arteries were induced in an organ bath by agonists or by electric field stimulation (EFS). Owing to divergent characteristics of both vessel types, EFS-induced contractions were only examined in interlobar arteries, and contractions by agonists acting on muscarinic receptors only in coronary arteries. NAV2729 inhibited frequency-dependent EFS-induced contractions of interlobar arteries. The degree of inhibition was similar using 5 µM and 10 µM NAV2729. Inhibition of EFS-induced contractions was resistant to a nitric oxide synthase inhibitor and to diclofenac. The neurogenic and adrenergic character of EFS-induced contractions was confirmed by inhibition by tetrodotoxin and prazosin. In coronary arteries, NAV2729 (5 µM) inhibited concentration-dependent contractions induced by carbachol and methacholine. Contractions induced by α 1 -adrenergic agonists, endothelin-1, the thromboxane receptor agonist U46619, or serotonin remained unchanged by NAV2729 in both vessel types. NAV2729 inhibits neurogenic contractions in interlobar arteries and contractions induced by cholinergic agonists in coronary arteries. In both vessel types, NAV2729 does not inhibit contractions induced by receptor agonists other than those acting on muscarinic receptors. Addressing effects in other vessels and in other smooth muscle–rich organs merits further attention.

Infectivity and antigenicity of pseudoviruses with high-frequency mutations of SARS-CoV-2 identified in Portugal - Hai-xin Wang; Li Zhang; Zi-teng Liang; Jian-hui Nie; Jia-jing Wu; Qian-qian Li; Ru-xia Ding; Yue Zhang; Guo-qing Chen; You-chun Wang; Hui-guo Wang; Wei-jin Huang (Archives of Virology, 2022)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has had a major impact on global human health. During the spread of SARS-CoV-2, weakened host immunity and the use of vaccines with low efficacy may result in the development of more-virulent strains or strains with resistance to existing vaccines and antibodies. The prevalence of SARS-CoV-2 mutant strains differs between regions, and this variation may have an impact on the effectiveness of vaccines. In this study, an epidemiological investigation of SARS-CoV-2 in Portugal was performed, and the VSV-ΔG-G* pseudovirus system was used to construct 12 spike protein epidemic mutants, D614G, A222V+D614G, B.1.1.7, S477N+D614G, P1162R+D614G+A222V, D839Y+D614G, L176F+D614G, B.1.1.7+L216F, B.1.1.7+M740V, B.1.258, B.1.258+L1063F, and B.1.258+N751Y. The mutant pseudoviruses were used to infect four susceptible cell lines (Huh7, hACE2-293T-293T, Vero, and LLC-MK2) and 14 cell lines overexpressing ACE2 from different species. Mutant strains did not show increased infectivity or cross-species transmission. Neutralization activity against these pseudoviruses was evaluated using mouse serum and 11 monoclonal antibodies. The neutralizing activity of immunized mouse serum was not significantly reduced with the mutant strains, but the mutant strains from Portugal could evade nine of the 11 monoclonal antibodies tested. Neutralization resistance was mainly caused by the mutations S477N, N439K, and N501Y in the spike-receptor binding domain. These findings emphasize the importance of SARS-CoV-2 mutation tracking in different regions for epidemic prevention and control.

Correction to: Inhibitory effects of aloperine on voltage-gated Na+ channels in rat ventricular myocytes - Meng-ting Li; Ya-ya Du; Fei Zhong; Jie-ru Wang; You-wei Gu; Yue Zhang; Xuan-tong Huang; Yi-zhou Deng; Zheng-xin Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Inhibitory effects of aloperine on voltage-gated Na+ channels in rat ventricular myocytes - Meng-ting Li; Ya-ya Du; Fei Zhong; Jie-ru Wang; You-wei Gu; Yue Zhang; Xuan-tong Huang; Yi-zhou Deng; Zheng-xin Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Vibrio nitrifigilis sp. nov., a marine nitrogen-fixing bacterium isolated from the lagoon sediment of an islet inside an atoll - Wei-Sheng Huang; Li-Ting Wang; Jwo-Sheng Chen; Yen-Ting Chen; Sean Ting-Shyang Wei; Yin-Ru Chiang; Pei-Ling Wang; Tzong-Huei Lee; Shih-Ting Lin; Lina Huang; Wung Yang Shieh (Antonie van Leeuwenhoek, 2021)

Purinergic smooth muscle contractions in the human prostate: estimation of relevance and characterization of different agonists - Annabel Spek; Bingsheng Li; Beata Rutz; Anna Ciotkowska; Ru Huang; Yuhan Liu; Ruixiao Wang; Frank Strittmatter; Raphaela Waidelich; Christian G. Stief; Martin Hennenberg (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)
Non-adrenergic prostate smooth muscle contractions may account for the limited effectiveness of α 1 -adrenoceptor antagonists, which are the first-line option for medical treatment of voiding symptoms suggestive of benign prostatic hyperplasia. In non-human prostates, purinergic agonists induce contractions reaching similar magnitudes as α 1 -adrenergic contractions. However, evidence for the human prostate is highly limited, and pointed to much weaker purinergic contractions. Here, we examined contractions of different purinergic agonists in human prostate tissues. Tissues were obtained from radical prostatectomy. Contractions were studied in an organ bath, and expression of purinergic receptors was studied by RT-PCR. Electric field stimulation (EFS)–induced contractions amounted to 104% of KCl-induced contractions (95% CI: 84–124%). From all tested agonists, only ATP induced concentration-dependent contractions, reaching an average maximum of 18% (12–24%) of KCl. Maximum tensions following application of other agonists averaged to 7.1% of KCl for α,β-methylene-ATP (1.8–12.4%), 3.9% for β,γ-methylene-ATP (2.0–5.4%), 3.1% for 2-methylthio-ATP (− 0.1–6.3%), and 5.1% for ATPγS (1.0–9.2%). Responses were not affected by the P2X antagonist NF023 or the P2Y antagonist PPADS. mRNA expression of P2X1-4 correlated with expression of a marker for catecholaminergic nerves, although neither ATP, NF023, nor PPADS changed EFS-induced contractions. Correlation between expression of receptors and the smooth muscle marker calponin was not observed. Our findings point to a low relevance of purinergic contractions in the human prostate, compared to other contractile stimuli in the human prostate and compared to purinergic contractions in non-human prostates. Purinergic contractions in the human prostate are not sensitive to NF023 or PPADS.

TRIP13 promotes the proliferation and invasion of lung cancer cells via the Wnt signaling pathway and epithelial–mesenchymal transition - Zhi-Han Li; Lei Lei; Liang-Ru Fei; Wen-Jing Huang; Yi-Wen Zheng; Mai-Qing Yang; Zhao Wang; Chen-Chen Liu; Hong-Tao Xu (Journal of Molecular Histology, 2021)

A comprehensive integrated transcriptome and metabolome analyses to reveal key genes and essential metabolic pathways involved in CMS in kenaf - Meiqiong Tang; Zengqiang Li; Dengjie Luo; Fan Wei; Muhammad Haneef Kashif; Hai Lu; Yali Hu; Jiao Yue; Zhen Huang; Wenye Tan; Ru Li; Peng Chen (Plant Cell Reports, 2021)

Characteristics of methane emissions in the Living Water Garden in Chengdu City from 2012 to 2017 - Ru Xue; Xiaoling Liu; Xiaoying Fu; Hongbing Luo; Ke Zhang; Bruce C. Anderson; Mei Li; Bo Huang; Lijuan Yu; Xiaoting Li; Shuzhi Fu; Aiping Pu; et al. (Environmental Science and Pollution Research, 2020)

Combined effect of polymorphisms of MTHFR and MTR and arsenic methylation capacity on developmental delay in preschool children in Taiwan - Yu-Mei Hsueh; Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Horng-Sheng Shiue; Ssu-Ning Chien; Chih-Ying Lee; Ming-I. Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2020)

Pure qP-wave least-squares reverse time migration in vertically transverse isotropic media and its application to field data - Jian-Ping Huang; Xin-Ru Mu; Zhen-Chun Li; Qing-Yang Li; Shuang-Qi Yuan; Yun-Dong Guo (Applied Geophysics, 2020)

Thioredoxin-Interacting Protein (TXNIP) Regulates Parkin/PINK1-mediated Mitophagy in Dopaminergic Neurons Under High-glucose Conditions: Implications for Molecular Links Between Parkinson’s Disease and Diabetes - Cun-Jin Su; Zhu Shen; Ru-Xiao Cui; Ya Huang; De-Lai Xu; Feng-Lun Zhao; Jie Pan; Ai-Ming Shi; Tong Liu; Yun-Li Yu (Neuroscience Bulletin, 2020)

The effective use of camera traps to document the northernmost distribution of the western black crested gibbon in China - Yi-Hao Fang; Yan-Peng Li; Guo-Peng Ren; Zhi-Pang Huang; Liang-Wei Cui; Li-Xiang zhang; Paul A. Garber; Ru-Liang Pan; Wen Xiao (Primates, 2020)

Applying multivariate statistics for identification of groundwater chemistry and qualities in the Sugan Lake Basin, Northern Qinghai-Tibet Plateau, China - Juan Xiang; Jun-ju Zhou; Jun-cang Yang; Mei-hua Huang; Wei Feng; Qiao-qiao Li; Dong-xiang Xue; Ya-ru Zhao; Guo-feng Zhu (Journal of Mountain Science, 2020)

Modified stepwise mini-incision microdissection testicular sperm extraction: a useful technique for patients with a history of orchidopexy affected by non-obstructive azoospermia - Peng Li; Chen-cheng Yao; Er-lei Zhi; Yuan Xu; Zhong Wan; Ying-chuan Jiang; Yu-hua Huang; Yue-hua Gong; Hui-xing Chen; Ru-hui Tian; Chao Yang; Liang-yu Zhao; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Development of Human in vitro Brain-blood Barrier Model from Induced Pluripotent Stem Cell-derived Endothelial Cells to Predict the in vivo Permeability of Drugs - Yuan Li; Xueying Sun; Houfu Liu; Liang Huang; Guofeng Meng; Yu Ding; Wenji Su; Jiaqi Lu; Sophie Gong; Georg C. Terstappen; Ru Zhang; Wandong Zhang (Neuroscience Bulletin, 2019)

Three new labdane-type diterpenoids from Callicarpa macrophylla Vahl. - Zhen-Hui Wang; Huan-Jun Xu; Yang-Yang Zhai; Lan-Ping Yang; Qiang Li; Mei Huang; Xing-Ying Chen; Wen-Kui Zhang; Yue-Li Meng; Qing-Ling Zhang; Chao Niu; Yan-Ru Zhang (Natural Product Research, 2019)

Association of plasma folate, vitamin B12 levels, and arsenic methylation capacity with developmental delay in preschool children in Taiwan - Ying-Chin Lin; Chi-Jung Chung; Ya-Li Huang; Ru-Lan Hsieh; Pai-Tsang Huang; Mei-Yi Wu; Pui-Lam Ao; Horng-Sheng Shiue; Shiau-Rung Huang; Chien-Tien Su; Ming-I Lin; Shu-Chi Mu; et al. (Archives of Toxicology, 2019)

Identification and characterisation of a glycine-rich RNA-binding protein as an endogenous suppressor of RNA silencing from Nicotiana glutinosa - Xu Huang; Ru Yu; Wenjing Li; Liwei Geng; Xiuli Jing; Changxiang Zhu; Hongmei Liu (Planta, 2019)

Soil physicochemical properties and vegetation structure along an elevation gradient and implications for the response of alpine plant development to climate change on the northern slopes of the Qilian Mountains - Yong-sheng Yang; Li Zhang; Hong-qin Li; Hui-dan He; Ya-xi Wei; Jin Luo; Guang-ru Zhang; Yu-ru Huang; Ying-nian Li; Hua-kun Zhou (Journal of Mountain Science, 2018)

TNF-α/TNFR1 Signaling is Required for the Full Expression of Acute and Chronic Itch in Mice via Peripheral and Central Mechanisms - Xiuhua Miao; Ya Huang; Teng-Teng Liu; Ran Guo; Bing Wang; Xue-Long Wang; Li-Hua Chen; Yan Zhou; Ru-Rong Ji; Tong Liu (Neuroscience Bulletin, 2018)

Modulation of ARTS and XIAP by Parkin Is Associated with Carnosic Acid Protects SH-SY5Y Cells against 6-Hydroxydopamine-Induced Apoptosis - Ru-Huei Fu; Li-Chun Huang; Chia-Yuan Lin; Chia-Wen Tsai (Molecular Neurobiology, 2018)

New phenolic acids from Salvia yunnanensis C.H.Wright - Yun Yu; Yin-ru Wang; Zhen-huan Dong; Wei Li; Shu-Ming Li; Xue-feng Huang (Natural Product Research, 2017)

Role of early environmental enrichment on the social dominance tube test at adulthood in the rat - Wen-Yu Cao; Zhao-Lan Hu; Yang Xu; Wen-Juan Zhang; Fu-Lian Huang; Xiao-Qing Qiao; Yan-Hui Cui; Wei Wan; Xue-qin Wang; Dan Liu; Ru-Ping Dai; Fang Li; et al. (Psychopharmacology, 2017)

Erratum to: Activation of the ventral tegmental area increased wakefulness in mice - Huan-Xin Sun; Dian-Ru Wang; Chen-Bo Ye; Zhen-Zhen Hu; Chen-Yao Wang; Zhi-Li Huang; Su-Rong Yang (Sleep and Biological Rhythms, 2017)

Early-Life Social Isolation-Induced Depressive-Like Behavior in Rats Results in Microglial Activation and Neuronal Histone Methylation that Are Mitigated by Minocycline - Hong-Tao Wang; Fu-Lian Huang; Zhao-Lan Hu; Wen-Juan Zhang; Xiao-Qing Qiao; Yan-Qing Huang; Ru-Ping Dai; Fang Li; Chang-Qi Li (Neurotoxicity Research, 2017)

Propofol attenuates H2O2-induced oxidative stress and apoptosis via the mitochondria- and ER-medicated pathways in neonatal rat cardiomyocytes - Xue-Ru Liu; Lu Cao; Tao Li; Lin-Lin Chen; Yi-Yan Yu; Wen-Jun Huang; Li Liu; Xiao-Qiu Tan (Apoptosis, 2017)

Cd Content in Sugarcane and Its Relationship with Soil Factors - Hui-Ping Ou; Liu-Qiang Zhou; Xi-Hui Liu; Jin-Sheng Huang; Yan Zeng; Ru-Lin Xie; Xiao-Hui Zhu; Hong-Wei Tan; Yang-Rui Li (Sugar Tech, 2017)

Activation of the ventral tegmental area increased wakefulness in mice - Huan-Xin Sun; Dian-Ru Wang; Chen-Bo Ye; Zhen-Zhen Hu; Chen-Yao Wang; Zhi-Li Huang; Su-Rong Yang (Sleep and Biological Rhythms, 2017)

Adenosine A2A receptors in the olfactory bulb suppress rapid eye movement sleep in rodents - Yi-Qun Wang; Rui Li; Dian-Ru Wang; Yoan Cherasse; Ze Zhang; Meng-Qi Zhang; Oriana Lavielle; Kristopher McEown; Serge N. Schiffmann; Alban de Kerchove d’Exaerde; Wei-Min Qu; Michael Lazarus; et al. (Brain Structure and Function, 2017)

Inhibition of the Receptor for Advanced Glycation End-Products (RAGE) Attenuates Neuroinflammation While Sensitizing Cortical Neurons Towards Death in Experimental Subarachnoid Hemorrhage - Hua Li; Jia-Sheng Yu; Ding-Ding Zhang; Yi-Qing Yang; Li-Tian Huang; Zhuang Yu; Ru-Dong Chen; Hong-Kuan Yang; Chun-Hua Hang (Molecular Neurobiology, 2017)

Dynamic quantitative proteomics characterization of TNF-α-induced necroptosis - Yang Wang; Zhi-Hao Huang; Yang-Jia Li; Gui-Wei He; Ru-Yuan Yu; Jie Yang; Wan-Ting Liu; Bin Li; Qing-Yu He (Apoptosis, 2016)

Salicylic acid-induced antioxidant protection against low temperature in cold-hardy winter wheat - Jing Yu; Jing Cang; Yanping Li; Ru Huang; Qiuwei Lu; Xiutian Wang; Lijie Liu; Qinghua Xu; Kejian Zhang (Acta Physiologiae Plantarum, 2016)

Molecular Design, Structural Analysis and Antifungal Activity of Derivatives of Peptide CGA-N46 - Rui-Fang Li; Zhi-Fang Lu; Ya-Nan Sun; Shi-Hua Chen; Yan-Jie Yi; Hui-Ru Zhang; Shuo-Ye Yang; Guang-Hai Yu; Liang Huang; Chao-Nan Li (Interdisciplinary Sciences: Computational Life Sciences, 2016)

Evaluating the impacts of cumulus, land surface and ocean surface schemes on summertime rainfall simulations over East-to-southeast Asia and the western north Pacific by RegCM4 - Yu-Bin Li; Chi-Yung Tam; Wan-Ru Huang; Kevin K. W. Cheung; Zhiqiu Gao (Climate Dynamics, 2016)

Deficient and excess dietary selenium levels affect growth performance, blood cells apoptosis and liver HSP70 expression in juvenile yellow catfish Pelteobagrus fulvidraco - Jun-Ru Hu; Yan-Hua Huang; Guo-Xia Wang; Ying-Xia Wu; Jian-An Xian; An-Li Wang; Jun-Ming Cao (Fish Physiology and Biochemistry, 2016)

Cloning, molecular characterization and functional analysis of a putative R2R3-MYB transcription factor of the phenolic acid biosynthetic pathway in S. miltiorrhiza Bge. f. alba - Gangping Hao; Xingyu Jiang; Lei Feng; Ru Tao; Yanling Li; Luqi Huang (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Tree bark as a biomonitor for the determination of polychlorinated biphenyls and polybrominated diphenyl ethers from Southern Jiangsu, China: levels, distribution, and possible sources - Li Zhou; Liang Dong; Ye-Ru Huang; Shuang-Xin Shi; Li-Fei Zhang; Xiu-Lan Zhang; Wen-Long Yang (Environmental Monitoring and Assessment, 2015)

Detection of gas hydrate sediments using prestack seismic AVA inversion - Ru-Wei Zhang; Hong-Qi Li; Bao-Jin Zhang; Han-Dong Huang; Peng-Fei Wen (Applied Geophysics, 2015)

Changes of polybrominated diphenyl ethers and polychlorinated biphenyls in surface soils from urban agglomeration of the Yangtze River Delta, in China between 2003 and 2012 - Shuang-Xin Shi; Ye-Ru Huang; Li Zhou; Li-Fei Zhang; Liang Dong; Wen-Long Yang; Xiu-Lan Zhang (Environmental Science and Pollution Research, 2015)

Characterization of 26 deletion CNVs reveals the frequent occurrence of micro-mutations within the breakpoint-flanking regions and frequent repair of double-strand breaks by templated insertions derived from remote genomic regions - Ye Wang; Peiqiang Su; Bin Hu; Wenjuan Zhu; Qibin Li; Ping Yuan; Jiangchao Li; Xinyuan Guan; Fucheng Li; Xiangyi Jing; Ru Li; Yongling Zhang; et al. (Human Genetics, 2015)

Comparative pharmacokinetics of oxytetracycline in blunt-snout bream (Megalobrama amblycephala) with single and multiple-dose oral administration - Ru-Qin Li; Yu-Wei Ren; Jing Li; Can Huang; Jun-hui Shao; Xiao-Xuan Chen; Zhi-Xin Wu (Fish Physiology and Biochemistry, 2015)

Studies on mitogen-activated protein kinase signaling pathway in the alveolar macrophages of chronic bronchitis rats - Yan Huang; Xiao-Ming Meng; Guo-Lin Jiang; Ya-Ru Yang; Juan Liu; Xiong-Wen Lv; Jun Li (Molecular and Cellular Biochemistry, 2015)

Increased prevalence of hepatitis C virus subtype 6a in China: a comparison between 2004–2007 and 2008–2011 - Xia Rong; Ru Xu; Huaping Xiong; Min Wang; Ke Huang; Qiuyu Chen; Chengyao Li; Qiao Liao; Jieting Huang; Wenjie Xia; Guangping Luo; Xin Ye; et al. (Archives of Virology, 2014)

Efficacy of a high-growth reassortant H1N1 influenza virus vaccine against the classical swine H1N1 subtype influenza virus in mice and pigs - Feng Wen; Hai Yu; Fu-ru Yang; Meng Huang; Sheng Yang; Yan-Jun Zhou; Ze-Jun Li; Guang-Zhi Tong (Archives of Virology, 2014)

Occurrence, sources, and ecological risks of PBDEs, PCBs, OCPs, and PAHs in surface sediments of the Yangtze River Delta city cluster, China - Ting Zhang; Wen-Long Yang; She-Jun Chen; Dian-Long Shi; Hu Zhao; Yi Ding; Ye-Ru Huang; Nan Li; Yue Ren; Bi-Xian Mai (Environmental Monitoring and Assessment, 2014)

SNP and haplotype analysis reveal IGF2 variants associated with growth traits in Chinese Qinchuan cattle - Yong-Zhen Huang; Zhao-Yang Zhan; Xin-Yi Li; Sheng-Ru Wu; Yu-Jia Sun; Jing Xue; Xian-Yong Lan; Chu-Zhao Lei; Chun-Lei Zhang; Yu-Tang Jia; Hong Chen (Molecular Biology Reports, 2014)

Ecological Risks Assessment and Pollution Source Identification of Trace Elements in Contaminated Sediments from the Pearl River Delta, China - Feng Li; Xiang-yun Zeng; Chang-hua Wu; Zhi-peng Duan; Yan-mao Wen; Guo-ru Huang; Xiao-lin Long; Min-Jian Li; Man-Jie Li; Jiang-Yu Xu (Biological Trace Element Research, 2013)

Inhibition of formyl peptide-stimulated phospholipase D activation by Fal-002-2 via blockade of the Arf6, RhoA and protein kinase C signaling pathways in rat neutrophils - Ya-Ru Tsai; Li-Jiau Huang; Hui-Yi Lin; Yun-Jie Hung; Miau-Rong Lee; Sheng-Chu Kuo; Mei-Feng Hsu; Jih-Pyang Wang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Molecular cloning, expression profiles and subcellular localization of cyclin B in ovary of the mud crab, Scylla paramamosain - Wen-Xing Li; Hui-Yang Huang; Jing-Ru Huang; Jin-Jin Yu; Jun Ma; Hai-Hui Ye (Genes & Genomics, 2013)

Polycyclic aromatic hydrocarbons in household dust near diesel transport routes - Chung-Yih Kuo; Heng-Chun Chen; Fang-Ching Cheng; Li-Ru Huang; Po-Shan Chien; Jing-Ya Wang (Environmental Geochemistry and Health, 2012)

Sex difference in QTc prolongation in chronic institutionalized patients with schizophrenia on long-term treatment with typical and atypical antipsychotics - Fu De Yang; Xiang Qun Wang; Xiu Ping Liu; Ke Xin Zhao; Wei Hong Fu; Xue Ru Hao; Xing Li Zhang; Guo Shu Huang; Sheng Cai Qu; Jing Shen Bai; Xu Feng Huang; Thomas R. Kosten; et al. (Psychopharmacology, 2011)

Asterotremella meifongana sp. nov. and Asterotremella nantouana sp. nov., two anamorphic basidiomycetous yeasts isolated from soil and mushrooms - Yi-Ru Liu; Li-Ying Huang; Suh-Shen Young; Chin-Feng Chang; Ching-Fu Lee (Antonie van Leeuwenhoek, 2011)

Simulation of organic carbon dynamics at regional scale for paddy soils in China - Xue-Zheng Shi; Ru-Wei Yang; David C. Weindorf; Hong-Jie Wang; Dong-Sheng Yu; Yao Huang; Xian-Zhang Pan; Wei-Xia Sun; Li-Ming Zhang (Climatic Change, 2010)

Estimates of individuals exposed to human metapneumovirus in a community-based Taiwanese population in 1999 - Chung-Guei Huang; Kuo-Chien Tsao; Tzou-Yien Lin; Yhu-Chering Huang; Li-Ang Lee; Tzu-Hou Chen; Ya-Ling Huang; Shin-Ru Shih (Archives of Virology, 2010)

Nematicidal Resorcylides from the Aquatic Fungus Caryospora callicarpa YMF1.01026 - Jinyan Dong; Yanhui Zhu; Hongchuan Song; Ru Li; Hongping He; Haiyang Liu; Rong Huang; Yongping Zhou; Le Wang; Yi Cao; Keqin Zhang (Journal of Chemical Ecology, 2007)